Feasibility of Layer Duck Farming in Wonomulyo Subdistrict, Polewali Mandar Regency - Ali, Najmah; Suhartina; Utami, Rahmawati Ning; Dahniar; Fadilah, Nur (Universitas Veteran Bangun Nusantara, 2025)
Duck egg farming is one of the important sources of income for rural communities, and the success of this business largely depends on cost efficiency and the level of profit obtained. This study aims to analyze the cost structure, revenue, and financial feasibility of duck egg farming in Wonomulyo Subdistrict based on the average data from 70 respondents. Data were collected through a survey method with structured interviews regarding the number of livestock, land area, production costs, and farm revenue. The results showed that the average number of ducks reared was 130 birds with an average land area of approximately 25 m² per farmer. Variable costs reached IDR 52,364,000 per year, while fixed costs amounted to IDR 5,190,000 per year, resulting in an average total production cost of IDR 57,554,000 per year. The average revenue from egg production was IDR 65,000,000 per year, yielding a net profit of IDR 7,446,000. Financial feasibility analysis indicated an R/C ratio of 1.13, a Break Even Point (BEP) of 28,777 eggs, and a Return on Investment (ROI) of 12.9% per year. These values demonstrate that duck egg farming is feasible to continue, as revenue exceeds production costs, profits are positive, and production is above the break-even point. The business can be further developed by improving cost efficiency and optimizing livestock productivity.